Novel Three-Dimensionally Printed Ultrasound Probe Simulator and Heart Model for Transthoracic Echocardiography Education - Bu, Yifan; Sharkey, Aidan; Bose, Ruma; Rehman, Taha Abdul; Saeed, Shirin; Khan, Adnan; Yunus, Rayaan; Mahmood, Feroze; Matyal, Robina; Neves, Sara (Journal of cardiothoracic and vascular anesthesia, 2023)
Simulation-based training is an essential component in the education of transthoracic echocardiography (TTE). Nevertheless, current TTE teaching methods may be subject to certain limitations. Hence, the authors in this study aimed to invent a novel TTE training system employing three-dimensional (3D) printing technology to teach the basic principles and psychomotor skills of TTE imaging more intuitively and understandably. This training system comprises a 3D-printed ultrasound probe simulator and a sliceable heart model. The probe simulator incorporates a linear laser generator to enable the visualization of the projection of the ultrasound scan plane in a 3D space. By using the probe simulator in conjunction with the sliceable heart model or other commercially available anatomic models, trainees can attain a more comprehensive understanding of probe motion and related scan planes in TTE. Notably, the 3D-printed models are portable and low-cost, suggesting their potential utility in various clinical scenarios, particularly for just-in-time training.